Analisis Nilai Tambah Produk Olahan Jagung Manis (Studi Kasus: Usaha F1 Aina Nagari Batu Hampa Kecamatan Akabiluru Kabupaten Lima Puluh Kota ) - Elva Rahmi Fitri; Zednita Azriani; Syahyana Raesi (Politeknik Pertanian Negeri Payakumbuh, 2021)
The aims of this research were to describe the processing of sweet corn, to analyze the value-added and distribution of value-added becomes peas,corn on the cob, donuts, grits, and bakwan on the business F1 Aina Batu Hampa. This study was conducted from March to April 2016. The study employed a case study method. The study used Hayami method in analyzing the value added. The results of this study showed that the value added generated by Aina F1 was high. It can be seen through the ratio of value added that is greater than 40 percent and varied among products where; 71.76 percents for corn peas, 58.65 percents for corn on the cob, 71.71percents for donuts, 74.40 percents for the grits, and 63,49 percents for bakwan. The product of Sweet corn that generate the highest value added is grits. The ratio of value added can be seen through the margin value distributed in production factors. The highest of portion of value-added received by the company and the smallest portion value-added received by the labor. The largest distribution margin is for the profit of the company. The company's biggest profits come from corn on the cob, followed by grits, peas, donuts, and bakwan. The largest distribution of other input contributions is bakwan, followed by donuts, peas, grits, and corn of the cob. The distribution of margins received by workers is the smallest part compared to the margins for other input contributions and company profits. The largest distribution is for bakwan , followed by donuts, peas, grits, and corn of the cob.